Design And Implementation Of A Situation Mapping Security System Using Multi-Factor Authentication Based On Fingerprint Biometrics: Rekamsiber - yelin_depondoye; Jeki Saputra; Yohanes Dwi Cahyono (Pustaka Poltekad, 2026)
This research centers on the development and deployment of a secure situation-mapping framework that integrates Multi-Factor Authentication (MFA) with biometric fingerprinting and the FIDO2 WebAuthn protocol. The project was initiated as a response to the growing sophistication of cyber threats—specifically phishing and unauthorized access—which pose a significant risk to sensitive territorial data.Adopting a Research and Development (R&D) methodology, the study progressed through systematic phases: requirement analysis, architectural design, implementation, and rigorous testing. The core of the system lies in its dual-layered defense, combining traditional credentials (username and password) with advanced biometric verification. To maintain high precision, the fingerprint matching process utilizes minutiae extraction paired with Euclidean distance calculations and rotation transformations. This technical approach ensures that verification remains accurate even when scanning positions are inconsistent.The implementation results demonstrate a marked improvement in both authentication speed and overall security. Furthermore, thorough white-box testing confirms that the architecture is resilient against common vulnerabilities, including SQL Injection and Cross-Site Scripting (XSS). Ultimately, the developed system provides a robust solution for data protection while significantly enhancing the operational efficiency of situation mapping management.